The Oxford handbook of psychology and spirituality - Miller, Lisa J. (Oxford library of psychology, 2014)
The Oxford Handbook of Psychology and Spirituality is an interdisciplinary reference for a rapidly emerging approach to contemporary science. This overarching work provides both a foundation and a roadmap for what is truly a new ideological age. Postmaterial spiritual psychology posits that consciousness can contribute to the unfolding of material events and that the human brain can detect broad, non-material communications.